2016
DOI: 10.1007/s00701-016-3046-3
|View full text |Cite
|
Sign up to set email alerts
|

A review of the clinical utility of serum S100B protein levels in the assessment of traumatic brain injury

Abstract: BackgroundIn order to improve injury assessment of brain injuries, protein markers of pathophysiological processes and tissue fate have been introduced in the clinic. The most studied protein “biomarker” of cerebral damage in traumatic brain injury (TBI) is the protein S100B. The aim of this narrative review is to thoroughly analyze the properties and capabilities of this biomarker with focus on clinical utility in the assessment of patients suffering from TBI.ResultsS100B has successfully been implemented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
204
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(212 citation statements)
references
References 200 publications
5
204
1
2
Order By: Relevance
“…NSE might be used as a prognostic marker in neuronal injury. Elevated NSE serum concentration correlates with a poor outcome in coma, especially caused by hypoxic insult (Thelin, Nelson, & Bellander, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSE might be used as a prognostic marker in neuronal injury. Elevated NSE serum concentration correlates with a poor outcome in coma, especially caused by hypoxic insult (Thelin, Nelson, & Bellander, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…NSE might be used as a prognostic marker in neuronal injury. Elevated NSE serum concentration correlates with a poor outcome in coma, especially caused by hypoxic insult (Thelin, Nelson, & Bellander, ). Several studies have shown that NSE yields a reliable estimate of the severity of neuronal injury as well as clinical outcome of patients with serious clinical manifestations such as in cases of stroke, head injury, anoxic encephalopathy, encephalitis, brain metastasis, and status epilepticus (Lima, Takayanagui, Garcia, & Leite, ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical utility of blood S100B levels in the assessment of traumatic brain injury has been recently reviewed (Thelin et al . ). In this case, an extra‐neural origin (namely adipose) for S100B in the blood appears to have a special relevance for the interpretation of results, since elevated S100B levels have also been shown in patients suffering from trauma in the absence of head injuries (Anderson et al .…”
Section: S100b As An Active Factor In Neural Injurymentioning
confidence: 97%
“…Both CSF and blood S100B levels are currently regarded as reliable biomarkers for acute brain injury caused by cardiovascular disorders or traumatic injury, and a predictive value for the outcome of these patients is also currently attributed to S100B levels in biological fluids (de Az ua L opez et al 2015 ;Chong 2016;Kellermann et al 2016). The clinical utility of blood S100B levels in the assessment of traumatic brain injury has been recently reviewed (Thelin et al 2017a).…”
Section: Acute Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation